HUBUNGAN DUKUNGAN ORANG TUA TERHADAP PRESTASI BELAJAR ANAK SD SELAMA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Oktaviani, Ni Kadek Yeyen; Puspita, Luh Mira; Devi, Ni Luh Putu Shinta (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023DO - 10.24843/coping.2023.v11.i06.p03, 2024)
Covid-19 pandemic has caused various changes in various aspects, one of which is in the education aspect. Changes in the learning system affect learning achievement. A student's learning achievement can be known by conducting a learning evaluation or an assessment of learning outcomes. Learning achievement is influenced by two factors, namely internal and external factors. The family in this case the parents is one of external factors that affect learning achievement. Parental support can be a factor that affects learning achievement. This study aims to determine the relationship between parental support and the learning achievement of elementary school children during online learning due to Covid-19 pandemic. This type of research is descriptive correlative with a cross sectional design. Samples were selected by using purposive sampling technique from grade 4 and 5 students at SD Negeri 8 Dauh Puri according to the inclusion and exclusion criteria totaling 130 people. Based on the results of the Spearman Rank test, the value of p=0,000 (p<0,05) means that there is a significant relationship between parental support and the learning achievement of elementary school age children during online learning during Covid-19 pandemic. The result value of r=0,754 indicates that the strength of the relationship between the variables of parental support and learning achievement is strong with a positive correlation direction. This means that the higher the parental support, the higher the learning achievement of elementary school children will be. Therefore, it is expected that parents can provide support, such us motivation, reward, information and facilities to their children as an effort to improve learning achievement at school.